West-East Railway Socioeconomic Observatory Project (OSFIOL): Engineering, Sustainable Territorial Development and Environmental Advances in Bahia (Research, Society and Development, 2025)
The article aims to propose the creation of the Socioeconomic Observatory of the West-East Integration Railway (OSFIOL) in the state of Bahia as an institutional strategy to strengthen democratic governance, social control, and promote sustainable development. The FIOL, of (inter)national relevance, aims to connect the productive interior of the West to Porto Sul in Ilhéus, Bahia, promoting economic and logistical gains, but also addressing socio-environmental and intermodal coordination challenges. The implementation of OSFIOL presents a technical and civic response to the needs of monitoring, evaluation, and proposal of related public policies. Using a methodology based on a bibliographic review and historical and documentary analysis, the study outlines the observatory's implementation phases, its conceptual foundations, theoretical bases, and administrative principles, in addition to highlighting the importance of its participatory and interdisciplinary management. It argues that socioeconomic observatories strengthen fiscal citizenship, transparency, and accountability, fostering integration between academia, government, and civil society. The experience of social observatories in Brazil, such as those in Maringá and Apucarana, is used as a benchmark for best practices. OSFIOL is expected to act as a civil society body focused on producing and disseminating reliable data, contributing to the efficient allocation of public resources and the mitigation of potential socioeconomic and environmental impacts, thus promoting an inclusive, ethical, and sustainable development model.